Direct Comparison of IR and DRI Detector for HT‐GPC of Polyolefins. Issue 1 (15th October 2015) - Honghong, Huang; Meifang, Guo; Dong, Wei; Suárez, Inmaculada; Coto, Baudilio; López, Esther; Ortín, Alberto; Yau, Wallace W.; Soares, João B. P.
Summary Molar mass distribution (MMD) of polyolefins is routinely analyzed by gel permeation chromatography (GPC), also known as size exclusion chromatography (SEC), practiced in different methods and detector systems. The filter‐based infrared detector (IR) has become a preferred alternative to the traditional use of differential refractive index detector (DRI) for high temperature GPC (HT‐GPC) when applied to polyolefins. The main reason is that a modern multiple band filter‐based IR detector can be used to determine the distribution of co‐monomer along the molar mass distribution in a copolymer, in a single HT‐GPC analysis directly without the need of additional analytical procedures. In addition to that, the performance of the modern IR detector when used as primary concentration detector in the HT‐GPC instrument, in either the single or the multiple detection schemes, proves to be superior to that of DRI detector. This is due to the high signal‐to‐noise ratio achievable by the modern IR detector and its excellent baseline stability. Such high detection quality can be attributed to the inherent robustness of IR spectroscopy against external factors such as GPC temperature and flow rate variations. The impact of that higher detection performance on the final processed analytical results of polymer MMD and molar mass averages among others, is the focus of this current investigation. Different application scenarios of industrial interest have been selected to show a direct comparison of both the IR and DRI detectors installed on a same GPC instrument.